Content Aspects of Professional Training of a Specialist in the Development of Individual Educational Trajectories - Antonina Andreeva; Svetlana Kalmykova; Irina Shoshmina (Education Sciences, 2022)
This article lists the prerequisites for the emergence of new interdisciplinary professions at the intersection of pedagogy, information and communication technologies. A new promising profession of a developer of individual educational trajectories is given, described in the “Atlas of New Professions 3.0”, developed under the auspices of the Agency for Strategic Initiatives. As conceived by the authors, this is a professional who creates a route for training new specialists from courses offered by educational institutions, including those available online, as well as simulators, simulators, internships, etc., and develops an educational track based on them, considering the psychotype, abilities and goals individual person. Since a brief description of this profession in the Atlas does not give a complete picture of its content, for the purposes of understanding the meaningful aspect of the professional training of such specialists in a multidisciplinary university, a description of the methodological basis of the developer of individual educational trajectories is given. The authors of this article describe the principle of operation of the constructor, developed at SPbPU and allowing the selection of the content of professional training of the developer of individual educational trajectories in a multidisciplinary university.